Release of Nitrogen from Granulate Mineral and Organic Fertilizers and Its Effect on Selected Chemical Parameters of Soil - Tomasz Niedziński; María José Sierra; Jan Łabętowicz; Kinga Noras; Cristina Cabrales; Rocio Millán (Agronomy, 2021)
The objective of this work was the evaluation of the release patterns of nitrogen from various types of fertilizers and their impact on selected chemical parameters of calcareous soil. Three mineral fertilizers and two organic fertilizers were tested in the laboratory for 35 days. This study showed the rapid release of nitrogen from mineral types. More than 70% of the nitrogen was released from the ammonium granules and 98% from the urea granules. The rate of nitrogen release from pellets of organic origin was much slower than from mineral pellets, the released N was 15–28% of the original amount. Soil pH was altered by incubation. The content of soil N changed significantly due to the incubation of N mineral fertilizers; no changes were observed for organic fertilizers. The EC value of the soil solution was significantly modified under the influence of mineral granules, it reached a maximum of 1147 µS cm−1 on the 10th day, and for organic fertilizers of 944 µS cm−1 on the 35th day. The results of this study characterize each N release pattern, providing data to support a more efficient nutrient management strategy in calcareous soils and the effect of incubated fertilizers on soil chemical parameters.